2020
DOI: 10.3390/app10248943
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrical Conductivity, Optical Property, and Stability of 2D MXene Nanofluid Containing Ionic Liquids

Abstract: The addition of ionic liquids with MXene nanofluid has a substantial impact on the solar thermal collectors’ working fluid’s optical properties that effectively absorb and distribute solar radiation. Increased solar radiation absorption potential ensures that heats are transported more rapidly and effectively. This research endeavors to investigate the concept of accumulating solar energy via the usage of ionic liquid-based 2D MXene nanofluid (Ionanofluids) for solar applications. In this study, the optical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…In addition, these properties are dependent on the dispersion stability of nanoparticles in base fluids. Therefore, the stability of the prepared ionanofluid is evaluated using a visual inspection method and Spectral absorbance method, which is briefly explained in our previous literature [38]. The results showed that the synthesized ionanofluids are highly stable for about 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these properties are dependent on the dispersion stability of nanoparticles in base fluids. Therefore, the stability of the prepared ionanofluid is evaluated using a visual inspection method and Spectral absorbance method, which is briefly explained in our previous literature [38]. The results showed that the synthesized ionanofluids are highly stable for about 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…PULSE mode is chosen with 20 s ON cycle and 10 s OFF cycle. A two-step method is more economical and easy; it was followed for preparing all the samples [37,38]. Due to the agglomerates' vibrations, which was caused by the ultrasonic waves, the temperature of the sample increased rapidly.…”
Section: Methodsmentioning
confidence: 99%
“…In parallel with surface modification with stabilizing ligands, introducing charg the surfaces of solar absorbers can induce the formation of electrical double layer to lize their dispersion within ionic liquids. For example, Bakthavatchalam et al [111 In parallel with surface modification with stabilizing ligands, introducing charges to the surfaces of solar absorbers can induce the formation of electrical double layer to stabilize their dispersion within ionic liquids. For example, Bakthavatchalam et al [111] prepared multi-layer MXene through a chemical etching route and dispersed them within the mixture of diethylene glycol and 1-ethyl-3-methyl imidazolium octyl sulfate ([Emim][OSO 4 ]) ionic liquid.…”
Section: Ionic Liquid-based Nanofluidsmentioning
confidence: 99%
“…For example, Bakthavatchalam et al [111 In parallel with surface modification with stabilizing ligands, introducing charges to the surfaces of solar absorbers can induce the formation of electrical double layer to stabilize their dispersion within ionic liquids. For example, Bakthavatchalam et al [111] prepared multi-layer MXene through a chemical etching route and dispersed them within the mixture of diethylene glycol and 1-ethyl-3-methyl imidazolium octyl sulfate ([Emim][OSO 4 ]) ionic liquid. The resultant nanofluids had shown stable uniform dispersion during the first 4 days.…”
Section: Ionic Liquid-based Nanofluidsmentioning
confidence: 99%
“…Bakthavatchalam et al [ 27 ] prepared nanocolloids based on 1-ethyl-3-methyl imidazolium octyl sulfate ionic liquid and measured their electrical conductivity, which was found to increase with the addition of MXene NPs, reaching 571 μS/cm.…”
Section: Introductionmentioning
confidence: 99%